Public Financial Management: A Bibliometric Analysis of Research Trends and Influential Publications - Muhammad Dimas Maulana; Raka Restu Mandese; Daiva Adyutasara; Muhammad Ramadhani Kesuma; Ellen D. Oktanti Irianto (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study conducts a comprehensive bibliometric analysis to map the global evolution of Public Financial Management (PFM) research, focusing on publication trends, geographic distribution, thematic clusters, and influential works shaping the field. Using data retrieved from the Scopus database and analyzed through VOSviewer and Bibliometrix, the study identifies a significant increase in PFM-related publications, particularly after 2010, driven by global demands for fiscal transparency, digital governance, and sustainable budgeting. The analysis reveals strong contributions from China, the United States, and several developing countries such as India and Brazil, while Indonesia remains underrepresented despite extensive fiscal reforms. Keyword co-occurrence mapping uncovers five major clusters, dominated by health sciences, environmental sustainability, and material engineering, with PFM themes embedded within broader clusters related to public health governance and fiscal sustainability. Seminal works by Wildavsky, Schick, and Allen & Tommasi continue to shape the intellectual foundations of PFM, influencing contemporary discourse on accountability, performance-based budgeting, and digital fiscal systems. Overall, the findings highlight the fragmented yet growing nature of PFM scholarship and underscore the need for more focused, context-rich research, especially in developing countries undergoing major public sector financial reforms.